Film Dan Poster Untuk Memperkuat Hubungan Antara Orang Tua Dan Remaja - Siswantara, Pulung (Jurnal Promosi Kesehatan Indonesia, 2010)
Background: Adolescents are individuals, either man or woman, who are in the middle of a transition period between childhood and adult. Adolescence is a period when individuals seek interpersonal relationships and involved sexual activities. Number of adolescent who infected by HIV is increase. Some of adolescent do some risky activity like premarital sexual interaction. Premarital sex among adolescent can prevent by strengthening parent and adolescent relationship. Message for strengthening relationship between family members could be shared by movie and poster with different target. Movie was targeted for adolescent because high exposure of movie in adolescence, and poster developed for parent because parent want simple and understandable message and poster can provided that. Method: This research is qualitative study with 2 steps, first step is literature review method for need assessment in media. Review did in 13 Articles (4 books, 2 journals, 5 researches, one articles and one presentation) in adolescence, parent and media. Second step is developing health promotion media, started from developing prototype, pretest and revision prototype. Result: From this research was developed movie titled â€œjangan biarkan mereka sendiriâ€. This movie depict social realistic about parent who ignore their child and result from ignorance. Target of this movie is adolescent between 11 until 15 years old or early adolescence. Expectation of this movie is adore adolescent for discuss with their parent about reproductive health, sexuality and their problem about reproductive health and their development. Poster show discuss between parent and adolescent and suggestion for starting talk to adolescent, be supported unity between picture, text, colur and content. Expetation from developing this poster is parent can discuss with their child about repruductive health, eith result paren can provide appropriate information, attitude and value in reproductive health.